Non-Linear Behaviour of Bolometric Detectors in Fourier Spectroscopy - David A. Naylor; Brad G. Gom; Scott C. Jones; Locke D. Spencer (Spring Optics and Photonics Congress Fourier Transform Spectroscopy Topical Meeting, 2009)
n/a